DNA barcodes reveal that the widespread European tortricid moth Phalonidia manniana (Lepidoptera: Tortricidae) is a mixture of two species - Mutanen, Marko; Aarvik, Leif; Huemer, Peter; Kaila, Lauri; Karsholt, Ole; Tuck, Kevin (Zootaxa, 2012)
During efforts to generate DNA barcodes for all North European Lepidoptera, Phalonidia manniana (Fischer vonRöslerstamm, 1839) was found to comprise two genetically distinct clusters. Morphological investigation further supportsthe existence of two distinct taxa, P. manniana and P. udana Guenée, 1845, sp. rev. Their biologies also differ, P. mannianafeeding in stems of Mentha and Lycopus (Lamiaceae) and P. udana feeding in stems of Lysimachia thyrsiflora and L.vulgaris (Primulaceae). We provide re-descriptions of both taxa and DNA barcodes for North European Phalonidia andGynnidomorpha. Phalonidia tolli Razowski, 1960, syn. nov., is considered a junior synonym of Pudana. Phalonidia udanais widely distributed in the North Palaearctic, whereas it seems to be rare or missing in large parts of Central Europe. The study demonstrates the usefulness of DNA barcoding in revealing cryptic species.